2006
DOI: 10.1089/hum.2006.17.415
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Replication-Deficient Recombinant Adenoviruses Encoding the Main Surface Antigens ofToxoplasma gondiiInduces Immune Response and Protection Against Infection in Mice

Abstract: We have generated recombinant adenoviruses encoding three genetically modified surface antigens (SAGs) of the parasite Toxoplasma gondii, that is, AdSAG1, AdSAG2, and AdSAG3. Modifications included the removal of their glycosylphosphatidylinositol (GPI) anchoring motifs and, in some cases, the exchange of the native signal peptide for influenza virus hemagglutinin signal sequence. Adenovirus immunization of BALB/c mice elicited potent antibody responses against each protein, displaying a significant bias towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Relative to their use in vaccine development, Ad-based vaccines have recently shown great promise in a number of applications that require elicitation of robust immune responses, such as combined humoral and cellular immune responses. [1][2][3][4][5][6] We have recently focused on Ad interactions with the complement system, and how these interactions may shape these important Ad-induced immune responses. Bars represent mean ± s.d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to their use in vaccine development, Ad-based vaccines have recently shown great promise in a number of applications that require elicitation of robust immune responses, such as combined humoral and cellular immune responses. [1][2][3][4][5][6] We have recently focused on Ad interactions with the complement system, and how these interactions may shape these important Ad-induced immune responses. Bars represent mean ± s.d.…”
Section: Discussionmentioning
confidence: 99%
“…More dramatically, recent demonstrations confirm the high efficacy and safe use of recombinant Ad (rAd)-based vaccines in infectious and acquired disease applications, including human immunodeficiency virus (HIV)-AIDS, Ebola, toxoplasmosis, H5N1 influenza and cancer. [1][2][3][4][5][6] Despite this widespread utility, little information is available regarding the mechanisms as to why rAds can elicit robust adaptive immune responses (both humoral and cellular). Although we, and others, have recently implicated intracellular signaling systems as mediating several important aspects of this response (that is, Ad interactions with the Toll-like receptor (TLR) system), it is also clear that instantaneous interactions of rAds with the extracellular pathogensensing complement system may also be significantly modulating these intracellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…Published reports of T. gondii specific CD8 + T cell responses are based on studies where animals were vaccinated mostly with major parasite protein, the surface antigens (SAG1-3). The resulting CD8 + T cells responded to either parasite lysate or to peptide restimulation in vitro ([11, 12, 13, 14] and references therein). Whether these potential SAG epitopes are generated in the course of a natural infection is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that homologous prime/boost protocols that use this vector to immunize mice are effective against Leishmania spp. (43), Toxoplasma gondii (10), or Trypanosoma cruzi (31) infections; they are all highly dependent on the induction of T-cell immunity for protection. Parasite-specific antibodies were also induced in all those animals.…”
mentioning
confidence: 99%